Encapsulation of Purple Sweet Potato Anthocyanins Using Alginate and Pectin as Natural Food Colorants - Hatimah, Husnul; Laga, Amran; Aristyarini, Rizki; Putra, Ardi Manggala (G-Tech: Jurnal Teknologi Terapan, 2026)
The use of non-food dyes is a problem in food safety. One of the efforts to solve this problem is the making of natural coloring products from purple sweet potato anthocyanin pigments. Anthocyanins are sensitive to oxidative damage, so encapsulation techniques need to be used to preserve bioactive compounds. Encapsulation with the coacervation method involves coating anthocyanins as the active ingredient with pectin and alginate as gel matrices, based on the principle of ionic gel formation. This study aimed to determine the optimal alginate concentration for the formation of anthocyanin encapsulates and to identify the color characteristics and interactions of the encapsulated anthocyanins from purple sweet potato. This study used various concentrations of alginate (0%, 0.5%, 1%, and 1.5%). The research parameters used were total anthocyanin and antioxidant activity (IC50). The findings indicated that the optimal concentration of alginate for preserving the solubility and stability of anthocyanin, derived from the bioactive compounds in purple sweet potatoes, was 1% alginate. This concentration resulted in a total anthocyanin content of 20.77 mg/L and an antioxidant activity (IC50) of 4049.73 ppm. A higher alginate concentration results in stronger gel formation; however, it simultaneously weakens the ability of alginate to bind anthocyanin as an active ingredient. This is attributed to the increase in viscosity, making the incorporation of the anthocyanin matrix into the encapsulates more difficult. Despite the very weak antioxidant activity, these anthocyanin encapsulates hold potential as natural food colorants for safe applications in acidic food products like beverages.